2020
DOI: 10.1038/s41598-020-68620-z
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale microlens arrays on flexible substrate with improved numerical aperture for curved integral imaging 3D display

Abstract: Curved integral imaging 3D display could provide enhanced 3D sense of immersion and wider viewing angle, and is gaining increasing interest among discerning users. In this work, large scale microlens arrays (MLAs) on flexible PMMA substrate were achieved based on screen printing method. Meanwhile, an inverted reflowing configuration as well as optimization of UV resin's viscosity and substrate's surface wettability were implemented to improved the numerical aperture (NA) of microlenses. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…To reduce unwanted iridescence over a wide range of viewing angles, angle-insensitive structural colour pixels 53 , 54 should also be designed and fabricated. In addition, the metalenses and structural colour pixels can be fabricated on curved substrates 55 instead of flat substrates. If high NA metalenses (NA ~1) are combined with angle-insensitive structural colour pixels of 250 nm pitch, a hyper-realistic LFP that provides a ~180° range of viewing angles and an angular resolution of 0.4° can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce unwanted iridescence over a wide range of viewing angles, angle-insensitive structural colour pixels 53 , 54 should also be designed and fabricated. In addition, the metalenses and structural colour pixels can be fabricated on curved substrates 55 instead of flat substrates. If high NA metalenses (NA ~1) are combined with angle-insensitive structural colour pixels of 250 nm pitch, a hyper-realistic LFP that provides a ~180° range of viewing angles and an angular resolution of 0.4° can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In direct methods, the lens is obtained from the base material. For example, the material directly shapes into the lens by the surface tension of the liquid or thermoplastic state of the material [2][3][4][5][6] . Although the direct methods are simple, cost-effective, and favorable for realizing super smooth curved surface of lens, it is difficult to precisely control the shape and size of the microlens as the lens geometry is determined by wettability, time, temperature, and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microlens arrays (MLAs) have attracted extensive attention due to their wide applications in various fields such as digital displays, [ 1–3 ] light‐emitting‐diodes (LEDs), [ 4,5,6,7 ] super‐resolution imaging, [ 8,9,10 ] and artificial compound eyes. [ 11,12,13 ] The demand of MLAs with precise shaping features has increased over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microlens arrays (MLAs) have attracted extensive attention due to their wide applications in various fields such as digital displays, [1][2][3] light-emitting-diodes (LEDs), [4,5,6,7] super-resolution imaging, [8,9,10] and artificial compound used to fabricate micro/nanolens arrays (M/NLAs). [13,28] Zhou et al reported that the diameters of the MLAs fabricated by E-jet printing decreased from 32.45 to 1.59 µm when the inner diameter of the nozzle decreased from 25 to 1 µm.…”
Section: Introductionmentioning
confidence: 99%